Answer:
my answer is 2x+ 3y=22 because that the answer
Answer:
x = -3/10
Step-by-step explanation:
Solve for x by substituting y = 3x into the other equation:
2x - 4y = 3
2x - 4(3x) = 3
Simplify and solve for x:
2x - 12x = 3
-10x = 3
x = -3/10
So, x = -3/10
Correct Answer:Second option
Solution:The given sequence is:
2.2, 6.6, 11, ...
If we observe the sequence it is an Arithmetic Sequence as the difference between two consecutive terms is the same.
6.6 - 2.2 = 4.4
11 - 6.6 = 4.4
First we find the general term for this sequence.
first term = 2.2
d = 4.4
So,
This general term will be placed inside the summation sign with limits from 1 to 5 to give the sum of first 5 terms of the given sequence. So the correct answer is Second Option
Answer:
3rd group of possible answers is the correct set
Step-by-step explanation:
Each of the three points in the 3rd line of possible answers is a solution of the given equation, as can be verified by substitution:
If x = -2, y = -8(-2) = +16
If x = 3, y = -8(3) = -24
If x = -4, y = -8(-4) = +32